2003
DOI: 10.3989/scimar.2003.67n3279
|View full text |Cite
|
Sign up to set email alerts
|

Fecundity of the common cuttlefish, <i>Sepia officinalis</i> L. (Cephalopoda, Sepiida): a new look at the old problem

Abstract: SUMMARY:The potential fecundity (PF) of advanced maturing and mature pre-spawning cuttlefish S. officinalis in the Aegean Sea varies from 3,700 to 8,000 (mean 5,871) oocytes, whereas the number of large yolk oocytes increases with mantle length from 130 to 839. Small oocytes predominate at all maturity stages. Spawning animals have a PF of some 1,000-3,000 eggs below that of pre-spawning females. This shows that intermittent spawning, which occurs in captivity, is a normal process in natural habitats. Empty fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 8 publications
2
23
0
Order By: Relevance
“…Histological analysis of pink cuttlefish ovaries revealed that oogenesis is asynchronous (sensu Rocha et al, 2001) and spawning likely is intermittent, as reported by Laptikhovsky et al (2003) for S. officinalis.…”
Section: Discussionmentioning
confidence: 78%
“…Histological analysis of pink cuttlefish ovaries revealed that oogenesis is asynchronous (sensu Rocha et al, 2001) and spawning likely is intermittent, as reported by Laptikhovsky et al (2003) for S. officinalis.…”
Section: Discussionmentioning
confidence: 78%
“…It may be expected that the smaller animals have a longer spawning period as a result of having larger eggs with higher fecundity depending on the low oviduct capacity. Laptikhovsky et al (2003) stated similar opinion for the correlation between the oviduct capacity and potential fecundity for an intermittent terminal spawner Sepia officinalis from the same family.…”
Section: Discussionmentioning
confidence: 83%
“…Size range of residual oocyte (0.1-7.5 mm) corresponds to that of viable oocytes in mature spawning individuals (Laptikhovsky et al 2003) and fit definition of the intermittent terminal spawning as assigned by Boletzky (1987). Even though the size of the animal gets larger there is no correlation with the amount of leftover residual oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Fecundity and spawning patterns are keystones of cephalopod reproduction and were studied across different taxa. There are numerous data on number of oocyte in prespawning females (Arkhipkin 1996, Boletzky 1987Forsythe et al 1994, Laptikhovsky & Arkhipkin 2001, Laptikhovsky & Nigmatullin 2005, Laptikhovsky et al 2003, Mangold-Wirz 1963, Melo & Sauer 1998, Nigmatullin & Markaida 2009) but very little is known about how many of them remain after spawning, so how efficiently the potential fecundity is used. The Common cuttlefish, Sepia officinalis (Linnaeus, 1758), was dubbed as a "white mouse" among cephalopods since it has been used for many laboratory studies (Boletzky 1983).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation